Intention of MSME in Rural Area Using Sharia Financing: The Influence of Sharia Financial Literacy, Entrepreneurial Characteristics, and Business Characteristics - Raharja, Mahardhika Cipta; Fahya, Angelliana Nur; Diana, Azka Nur (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study aims to determine the effect of sharia financial literacy, entrepreneurial characteristics and business characteristics on intention in using sharia financing. this research is a quantitative study with data collection techniques through distributing questionnaires to respondents. The population in this study are MSME players in the Purwokerto area who know about sharia financing. The sampling technique used Accidental Sampling technique with 110 respondents. Data processing in this study used multiple linear regression analysis using the SPSS program. Based on the results of the study, it can be concluded that sharia financial literacy has no effect on intention in using sharia financing with a significant value of 0.128 > 0.05. Entrepreneurial characteristics affect the intention in using sharia financing with a significant value of 0.006 < 0.05. And business characteristics have no effect on intention in using sharia financing with a significant value of 0.069 > 0.05.